Secure circuit with optical energy harvesting against unpowered physical attacks. (August 2018) - Kim, Hyungseup; Ko, Youngwoon; Mun, Yeongjin; Lee, Byeoncheol; Kim, Dong Kyue; Choi, Byong-Deok; Kim, Ji-Hoon; Ko, Hyoungho
Abstract: This study presents an optical secure circuit for physical attack protection. On-chip photodiodes are integrated for optical energy harvesting to operate the optical secure circuit in a standard CMOS process. The aim of the proposed optical secure circuit is to protect the secure contents of the IC against external unpowered attacks. When invasive unpowered physical attacks such as decapsulation are attempted, the photodiodes accumulate charge from ambient light and activate the secure circuit path that shuts down the secure data path. The proposed secure circuit is fabricated using a standard 0.18 µm 1P6M CMOS process with a small active area of 0.34 mm 2 with fully integrated on-chip photodiodes. When the chip is decapsulated and unpowered, the supply voltage of 600 mV with the ambient light is generated by the optical harvester, and the security data paths are shut down in 500 ns.